Jeremy Bentham's Demopticon. Prospects for democratic surveillance based on the Panopticon - Marchesin, Leonardo (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2025)
In the field of surveillance studies, Jeremy Bentham's Panopticon is often identified as a theoretical model of a surveillance, the contemporary one, considered detrimental to the individual and, above all, to democratic life. Such a view, indebted to the main historical reconstructions concerning the genesis of the Englishman's Inspection House and to Michel Foucault's interpretation of it, nevertheless fails to contextualise the Panopticon within the political thought of Bentham, who was a great advocate of representative democracy. Reconstructing Englishman's socio-political reflection may allow, therefore, for the recognition of a less despotic nature to the Inspection-house, which could begin to be considered no longer as a model for describing past or potential tyrannical regimes, but as a paradigm for beginning to design surveillance more consistent with democratic principles.